Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441308
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for drop performance prediction and application for design optimization of chip scale packages

Abstract: As handheld electronic products are more prone to being dropped during useful life, package to board interconnect reliability has become a major concern for these products. This has prompted the industry to evaluate the drop performance of CSP packages while mounted on printed wiring boards using board level drop testing.Although a new board level test method has been standardized through JEDEC (JESD22-B111), characterization tests take quite a long time to complete, extending the design cycle. This paper prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Thus, the damage may be as significant as the contribution due to differential flexing between the PCB and IC package. Syed et al [8] also showed the joint failure in the IC packages across the PCB is location dependent. In accelerated thermal cycling tests, the temperature excursion between C and C had caused concurrent degradation of the solder joint resulting in intermetallic compound (IMC) growth [16] and thermal fatigue damage [17].…”
Section: Evaluation On Influencing Factors Of Board-levelmentioning
confidence: 95%
“…Thus, the damage may be as significant as the contribution due to differential flexing between the PCB and IC package. Syed et al [8] also showed the joint failure in the IC packages across the PCB is location dependent. In accelerated thermal cycling tests, the temperature excursion between C and C had caused concurrent degradation of the solder joint resulting in intermetallic compound (IMC) growth [16] and thermal fatigue damage [17].…”
Section: Evaluation On Influencing Factors Of Board-levelmentioning
confidence: 95%
“…Due to the large deformation constituted by both the bending and twisting modes, the solder joints experienced the highest level of stress where all the solder joints failed below the drop cycles of twenty. Study by Syed et al [8] revealed similar observation. In their test the PCB is fully populated with fifteen components, and solder joints at location #14 (refer to Fig.…”
Section: Drop Test Results and Trendssupporting
confidence: 70%
“…Thus the damage may be as significant as the contribution due to differential flexing between the PCB and IC package. Syed et al [8] also showed the joint failure in the IC packages across the PCB is location dependent.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Coffin-Manson) to predict failures in involved the falling mass impacting the PCB indirectly a JEDEC standard drop test [22]. The first and largest peak of through a four-point loading fixture.…”
Section: Introductionmentioning
confidence: 99%